Literature Review: Conservative Acupuncture Treatment for Infertility Causes in Asia - Nashriati, Fatma; Sri Rejeki, Dwi Sarwani; Mars Wijayanti, Siwi Pramatama (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2025)
Failure to conceive within a year of frequent, unprotected sexual activity is known as infertility, and it can be caused by a variety of conditions or unexplained causes. A common non-pharmacological therapy approach, acupuncture is a crucial part of complementary and alternative medicine. Acupuncture may be able to boost the reproductive system’s performance and regulate the body’s hormones by activating particular acupoints. This systematic review followed the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guidelines. This study aims to identify conservative acupuncture treatment for infertility causes because there isn’t a clear summary of acupuncture and infertility with different infertility issues in Asia. A comprehensive search was performed across several database including Pubmed, Google Scholar, Scopus. The search was limited to studies published between 2019 and 2024 which were written in English. The study shows that infertility in both men and women can be improved with acupuncture treatment. By stimulating specific acupuncture sites, acupuncture may be able to better control the body’s hormones and enhance the reproductive system’s function. We found that, for both men and women, acupuncture therapy can aid with infertility